Prevalence of urinary tract infection in 2-8-week-old infants with jaundice - Partini Trihono; Arfianti Chandra Dewi; Hartono Gunardi; Hanifah Oswari (Paediatrica Indonesiana, 2012)
Background Urinary tract infections (UTI) in infants may manifest in various ways and often appear without symptoms.Â Previous studies have reported that j aundice has been observed inÂ infants aged less than 8 weeks 'With UTIs. However, a prospectiveÂ study on the prevalence of UTI in infants with jaundice aged 2ô€‚8weeks is warranted in order to improve diagnosing capability andÂ provide prompt treatment.Objective To investigate the prevalence and profiles of UTI inÂ infants with jaundice aged 2ô€‚8 weeks.Methods This crossô€‚sectional study was carried out in June-December 2011 in infants with jaundice aged 2ô€‚8 weeks. Subjects were patients from the Department of Child Health,Â Cipto Mangunkusumo Hospital (CMS), as well as the PediatricÂ Polyclinics ofBudi Kemuliaan and Thamrin Hospitals. All subjectsÂ underwent total, direct and indirect bilirubin examinations,Â urinalyses and urine cultures.Results Of the 110 subjects recruited, the prevalence of UTIÂ was 18.2%. More boys than girls had UTIs (13 boys, 7 girls). TheÂ microorganisms found in subjects v.ith UTIs were Escherichia coliÂ (10/20), Klebsiella pneumoniae (8/20), and Enterobacter aerogenesÂ (2120). Indirect hyperbilirubinemia was found in 5/20 subjects.Â There were more subjects with UTIs in the nonô€‚exclusivelyÂ breastfed (8/20) and nonô€‚breastfed (8/20) groups than in theÂ exclusively breastfed group (4/20), the full term gestational ageÂ (GA) group (17/20) than the pretenn GA group (3/20), and theÂ normal birth weight group (15/20) than the low birth weight group (5/20). The median age of jaundice onset was 3.5 daysÂ (range lAO days), and the median duration of jaundice was 13.5Â days (range 3-56 days).Conclusion The prevalence of UTI in infants aged 2ô€‚8 weeksÂ v.ith jaundice was 18.2%. More boys than girls had UTIs. TheÂ most common infecting microorganism found in our subjects wasÂ Escherichia coli. In daily medical practice, infants with prolongedÂ jaundice of more than 2 weeks should be tested byurin alysisÂ and urine cultures for the presence of UTIs. [Paediatr Indones.2012;52:304-8].